Translation Errors and the Strategies to Overcome them: A Case Study of Captions of Museum Displays in Yogyakarta - Zakia El Muarrifa (Lexicon, 2015)
Museums play an important role to an area, especially in Yogyakarta, not only as a place where they keep historical, scientific, or artistic artefacts, but also as a tourism destination. Tourists from inside as well as outside of Indonesia come to these museums to educate themselves about Yogyakarta, which is famous as a “student city” and “cultural city”. However, visitors from overseas may get confused with the translation provided since many translation errors are found in the captions of museum displays. In this paper, I am going to identify, analyze and discuss the meaning based translation errors in Museum Sonobudoyo and Museum Kraton Kasultanan Ngayogyakarto Hadiningrat, and classify them to find out what most common mistakes the translators make are. After identifying and classifying the errors, the paper will move onto how to tackle the cultural-specific concept errors using note, a translation procedure by Newmark (1988) and translation steps by Larson (1998) for the non-cultural-specific concept problems.